PEMODELAN GEOGRAPHICALLY AND TEMPORALLY WEIGHTED REGRESSION PADA PRODUK DOMESTIK REGIONAL BRUTO - Ramadhan, M. Rizky; Yurinanda, Sherli; Sarmada (Universitas Insan Budi Utomo, 2026)
Regional development aims to promote economic growth in society, which is commonly measured using Gross Regional Domestic Product (GRDP). Sumatra Island is one of the regions that makes a substantial contribution to national economic growth. However, compared to other provinces in Sumatra, Jambi Province still records a relatively lower GRDP value. In addition, GRDP growth among regencies/municipalities in Jambi Province shows disparities and fluctuates from year to year. This condition reflects variations in the influence of economic factors both spatially and temporally. Spatial variation is indicated by the interregional linkage of GRDP and differences in the economic characteristics of each area, while temporal variation is observed through changes in annual GRDP growth influenced by commodity price fluctuations, development projects, and local economic dynamics. If the analysis is conducted using conventional linear regression without considering spatial and temporal aspects, it may violate classical assumptions, such as the presence of heteroskedasticity, residual autocorrelation, and the inability of the model to capture the dynamics of GRDP changes. This may result in biased and less valid coefficient estimates. This study aims to analyze the effects of Domestic Investment, Human Development Index (HDI), Labor Force Participation Rate (LFPR), Local Own-Source Revenue, and Capital Expenditure on the GRDP of regencies/municipalities in Jambi Province during the 2021–2024 period using the Geographically and Temporally Weighted Regression (GTWR) method. The analysis is carried out through testing spatial and temporal effects, determining the weighting function, estimating parameters, and evaluating model goodness-of-fit using the AIC and R² values. The results show that the GTWR model yields an AIC value of 90.93 and an R² value of 0.526.